Lower Ferrum, Selenium, and Cadmium; Higher Chromium and Lead Levels in Preeclampsia Patients’ Erythrocyte: A Cross-Sectional Study - Sandhy Prayudhana; Damar Prasmusinto; Noroyono Wibowo; Rima Irwinda; Yuditiya Purwosunu; Yudianto Budi Saroyo (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Oxidative stress and trace elements in erythrocytes are linked to impaired nitric oxide that can lead to endothelial dysfunction in preeclampsia patients. The morphology of erythrocytes could also be affected by oxidative stress and trace elements. While the relationships between erythrocyte index, superoxide dismutase (SOD) activity, and oxidative stress in preeclampsia have been well established, less attention has been given to the erythrocyte trace elements and their role in disease progression. This study was performed to examine the erythrocyte trace element profile in women with preeclampsia, comparing it with controls. Additionally, it will explore the correlations between erythrocyte trace element levels, the erythrocyte index, and SOD activity.METHODS: A cross-sectional study was conducted involving 40 pregnant women consisting of those with severe preeclampsia and normotensive. Erythrocytes was isolated from blood samples, and analysis of erythrocyte SOD activity and trace elements were performed using the enzyme linked immunosorbent assay (ELISA) and inductively coupled plasma mass spectrometry (ICP-MS), respectively.RESULTS: Among 15 examined erythrocyte trace elements, the levels of ferrum (Fe), selenium (Se), and cadmium (Cd) were significantly lower, meanwhile, the levels of chromium (Cr) and lead (Pb) were significantly higher in preeclampsia subjects. Additionally, preeclampsia subjects exhibited smaller erythrocyte sizes compared to the normotensive subjects. The erythrocyte SOD activity was significantly elevated in the preeclampsia subjects than the normotensive subjects.CONCLUSION: Erythrocyte trace element levels of Fe, Se, Cd, Cr, and Pb were significantly altered in preeclampsia compared to normotensive controls. These findings suggest that these trace elements may serve as potential predictors for preeclampsia.KEYWORDS: preeclampsia, trace elements, antioxidant, oxidative stress, superoxide dismutase, erythrocyte index